2004
DOI: 10.1021/jp047788i
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Water from First Principles:  Investigation of Different Sampling Approaches

Abstract: A series of first principles molecular dynamics and Monte Carlo simulations were carried out for liquid water to investigate the reproducibility of different sampling approaches. These simulations include Car−Parrinello molecular dynamics simulations using the program cpmd with different values of the fictitious electron mass in the microcanonical and canonical ensembles, Born−Oppenheimer molecular dynamics using the programs cpmd and cp2k in the microcanonical ensemble, and Metropolis Monte Carlo using cp2k i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
406
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 343 publications
(442 citation statements)
references
References 40 publications
33
406
1
2
Order By: Relevance
“…The present results are also relevant to those of a very recent ab initio molecular-dynamics study of liquid water at 315 K. 55 This study employed the Becke-Lee-Yang-Parr 56,57 ͑BLYP͒ density functional in a number of independent simulations of systems of 64 and 128 water molecules. The resulting self-diffusion coefficient was found to be 0.04± 0.02 Å 2 / ps-nearly an order of magnitude smaller than the experimental value of 0.35 Å 2 /ps at 315 K. 58 Insofar as we can tell from the present results, quantummechanical effects in the nuclear motion and finite-size effects are unlikely to be the only causes of such a large discrepancy.…”
Section: Discussionmentioning
confidence: 52%
“…The present results are also relevant to those of a very recent ab initio molecular-dynamics study of liquid water at 315 K. 55 This study employed the Becke-Lee-Yang-Parr 56,57 ͑BLYP͒ density functional in a number of independent simulations of systems of 64 and 128 water molecules. The resulting self-diffusion coefficient was found to be 0.04± 0.02 Å 2 / ps-nearly an order of magnitude smaller than the experimental value of 0.35 Å 2 /ps at 315 K. 58 Insofar as we can tell from the present results, quantummechanical effects in the nuclear motion and finite-size effects are unlikely to be the only causes of such a large discrepancy.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, various physical effects such as van der Waals interactions between molecules and the quantum behaviour of nuclei have to been reproduced only approximately or even completely neglected. In addition, the high computational cost of AIMD imposes severe restrictions on the size of a model system and time length of the simulations thus introducing additional finite-size errors and statistical uncertainties into the properties calculated [99][100][101][102][103][104][105][106][107] .…”
Section: Liquid Water a Structural And Dynamical Properties Of Lmentioning
confidence: 99%
“…For the solution of the SCF equations, we used an optimizer based on orbital transformations, which scales linearly in the number of basis functions [55]. It has been already demonstrated that this optimization algorithm, in combination with the GPW linear scaling calculation of the Kohn-Sham matrix, can be used for applications with several thousands of basis functions [56]. Geometry optimizations have been carried out using the Broyden-Fletcher-Goldfarb-Shanno minimization algorithm 5 (BFGS) [57][58][59][60][61], and the structures have been optimized until the atomic displacements were lower than 3 · 10 −3 Bohr and the forces lower than 4.…”
Section: Gaussian and Plane Wave Calculationsmentioning
confidence: 99%